Akuntabilitas Pengelolaan Keuangan Di Desa Pasir Lhok Aron Kecamatan Johan Pahlawan Kabupaten Aceh Barat - Duinta Putri; Nabilla Hilmy Zhafira (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
This research was carried out in the Village with the aim of knowing the accountability of village financial management in which the types of research indicators include planning, implementation, changes in APBDes, and transparency of accountability reports for management. The research methods, and field observations using comparative financial management in the Village of Pasir Lhok Aron and by adjusting the Aceh Barat Regegent’s Regulations Number 20 of 2018 concerning village financial management. The technique that the researcher uses in collecting this data is using interviews and the researcher makes direct observations of the object under study. The results of this study show that the basis for the Regent’s Regulation Number 20 of 2018 concerning overall village financial management in the Village of Pasir Lhok Aron has achieved accountability. They also assisted the village in continuing to strive for the realization of village financial management accountability in the village of Pasir Lhok Aron.